A Study on the welfare measures and their Impact on QWL provided by the Sugar companies with reference to East Godavari District, Andhra Pradesh, India - P V V, Satyanarayana (Journal of Management and Science, 2011)
The Sugar factories play a vital role in human life. Sugar industry is one of the important industries of India for earning Foreign Exchange and giving employment to lakhs of workers. Because of being highly labour intensive industry it needs to concentrate more in the area of employee‟s welfare measures. East Godavari District in Andhra Pradesh, India has taken as a sample for this study, for identifying various methods and also to identify the effectiveness of the methods. The study shows that 15% of the employees are highly satisfied with their welfare measures. 22% of the employees are satisfied with their welfare measures. 39% of the employees are average with their welfare measures. 16% of them are in highly dissatisfied welfare measures play an important role in employee satisfaction and it results in improved quality of work life. This study throws light on the impact of welfare measures on QWL among the employees of Sugarfactories in Andhra Pradesh.